2017
DOI: 10.3390/membranes7010011
|View full text |Cite
|
Sign up to set email alerts
|

Fogging Control on LDPE/EVA Coextruded Films: Wettability Behavior and Its Correlation with Electric Performance

Abstract: The transformation of fog at a non-visible water layer on a membrane of low-density polyethylene (LDPE) and ethylene-vinyl acetate (EVA) was evaluated. Nonionic surfactants of major demand in the polyolefin industry were studied. A kinetic study using a hot fog chamber showed that condensation is controlled by both the diffusion and permanency of the surfactant more than by the change of the surface energy developed by the wetting agents. The greatest permanency of the anti-fog effect of the LDPE/EVA surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…PDMS and EVA are hydrophobic with advancing contact angles of 117 and 100°, respectively. The contact angle for PDMS matches exactly the value reported by Shahsavan et al 43 The contact angle measured for EVA is higher by about 7°than that reported by WaldoMendoza et al 44 The elevated roughness of the EVA sample (Table 1) is likely responsible for this difference in contact angle. Nylon and PET are under the category of hydrophilic polymers, 45,46 with advancing contact angles of about 63 and 77°, respectively.…”
supporting
confidence: 77%
“…PDMS and EVA are hydrophobic with advancing contact angles of 117 and 100°, respectively. The contact angle for PDMS matches exactly the value reported by Shahsavan et al 43 The contact angle measured for EVA is higher by about 7°than that reported by WaldoMendoza et al 44 The elevated roughness of the EVA sample (Table 1) is likely responsible for this difference in contact angle. Nylon and PET are under the category of hydrophilic polymers, 45,46 with advancing contact angles of about 63 and 77°, respectively.…”
supporting
confidence: 77%
“…Nowadays, polymeric films are widely used in various fields including food packaging, medical equipment, aerospace industry, and agricultural production 1‐4 . Plastic films are one of the best choices as packaging material for food packaging and agricultural greenhouse coverage because their simple production process and low cost 3 .…”
Section: Introductionmentioning
confidence: 99%
“…have worked on the modification of XLPE exposed to partial discharges at elevated temperature. Waldo‐Mendozae et al . have examined the effect of the different nonionic surfactants on the wetting behavior of the LDPE/EVA coextruded films.…”
Section: Introductionmentioning
confidence: 99%